Chlorhexidine-alcohol versus Povidone-iodine plus Alcohol as Preoperative Antiseptic for Prevention of Surgical Site Infection in Caesarean Section: A Randomised Controlled Trial - Shravanthi Swamy; Aruna M Biradar; Ekta Chhabra; Shailaja Rajendra Bidri; Neelamma Patil; Shreedevi Kori; Shilpa Lakshmi; Preethi Malapure (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Caesarean Section (CS) is one of the most commonly performed surgical procedures worldwide, with its incidence steadily increasing. Surgical Site Infection (SSI) remains a significant complication, impacting maternal recovery and healthcare costs. Aim: To evaluate the efficacy of chlorhexidine-alcohol versus Povidone-Iodine (PI) plus alcohol in preventing SSI in patients undergoing CS. Materials and Methods: This Randomised Controlled Trial (RCT) was conducted in the Department of Obstetrics and Gynaecology from April 2024 to April 2025 at a tertiary care centre, Shri B.M. Patil Medical Hospital and Research Centre, Bijapur, Karnataka, India. A total of 208 pregnant women undergoing CS were enrolled and randomly assigned to two groups: Group A received preoperative skin preparation with chlorhexidine-alcohol, while Group B received PI followed by surgical spirit. Postoperative wound assessment was conducted on day 2, and wounds were cleaned and dressed using sterile Sterizone (a transparent film dressing with a silver lining). Follow-up inspections occurred on day 5, day 7, or at discharge whichever was later. In cases of wound discharge, swabs were sent for culture and sensitivity. Outcomes assessed included incidence of SSI, wound discharge, and need for additional interventions. Statistical analysis was conducted using John’s Macintosh Project (JMP)-Statistical Analysis System (SAS) software version 17. Continuous variables were compared using the independent t-test, and categorical data using the Chi-square test. A p-value<0.05 was considered statistically significant. Results: The incidence of superficial SSI was significantly lower in the chlorhexidine group compared to the PI group (1.0% vs. 8.7%, p-value=0.018). Similarly, deep infections were less frequent in the chlorhexidine group (1.9% vs. 2.9%, p-value=0.018). There was no significant difference between groups regarding the types of organisms isolated (p=0.0966). Staphylococcus aureus was the most commonly isolated pathogen (1.9% in both groups). Conclusion: Chlorhexidine-alcohol demonstrated superior efficacy in reducing SSI compared to PI in patients undergoing CS. The present finding supports the use of chlorhexidine-alcohol as the preferred preoperative antiseptic for caesarean deliveries.